Implante intraperitonial de tela de polipropileno revestida de hidrogel de poli (2-hidroxietil metacrilato) em cães aspecto histológico - SILVA, Daniel Barbosa da (2010)
Abdominal wall defects may occur in fairly all animal species, and frequently demand corrective surgical treatment including implants of meshes, such as polypropylene. However, this biomaterial is not free from complications, what stimulates constant researches for new biomaterials that present certain advantages. Due to its well known biocompatibility, poliHEMA hydrogel was the chosen biomaterial for experimental abdominal wall implant associated to polypropylene mesh. This essay compared tissue responses to the employment of polypropylene mesh alone (group PP) and polyHEMA Hydrogel film associated to polypropylene mesh (group PH) on the correction of induced abdominal wall defects on bitches. Twelve mongrel adult female dogs, weighting from 10 to 20 kg, were divided in two equal groups. The animals from group PP received the polypropylene mesh implant whilst those from group PH received polyHEMA hydrogel coated polypropylene mesh to replace the abdominal transverse muscle. Six animals from each group were submitted to surgical procedure to remove the meshes at 30 and 60 days of the postoperative period. Tissue repairing phenomena such as: chronic inflammatory reaction, giant cell presence (foreign body chronic granulomatous inflammatory reaction) and connective tissue proliferation were microscopically evaluated. It may be concluded that polyHEMA hydrogel as a coating agent on polypropylene mesh implanted onto abdominal wall of female dogs triggers greater deposition of type I collagen, than polypropylene mesh alone.